Optical Technologies Applied to Cultural Heritage - Vazquez-Molini, Daniel; Fernandez-Balbuena, Antonio Alvarez (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A short book about different issues in optical technologies. The importance of optical technologies for artwork charaterization is well known, in this book we show some examples where different optical technologies are applied in real cultural heritage artworks.